THE EFFECT OF PUGUNTANO (CURANGA FEL-TERRAE [LOUR.]) EXTRACT ON ADIPONECTIN RECEPTOR (ADIPOR) IN RATS WITH TYPE 2 DIABETES MELLITUS - LINDARTO, DHARMA; MACHRINA, YETTY; SYAFRIL, SANTI; SARAGIH, AWALUDDIN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study aimed to determine whether the antidiabetic effects of puguntano (Curanga fel-terrae [Lour.]) extract involve anti-inflammatory effects mediated through adiponectin receptors (AdipoRs). Methods: Type 2 diabetes mellitus (T2DM) Wistar rats were induced by a combination of high-fat diet for 5 weeks and injection small dose streptozotocin 30 mg/kg bw/rat. This study was conducted in 48 T2DM rats, which were randomly assigned into two weight-matched groups (n=24, each). Only the treatment group received 0.2 mg/g bw of puguntano extract suspension through oral for 10 days. The clinical characteristics of T2DM and AdipoR were assessed before and after the treatment period. Results: The treatment group demonstrated significantly lower body weight, fasting blood glucose, and homeostasis model assessment-insulin resistance (HOMA-IR) but higher AdipoR than the control group (all, p<0.001). Furthermore, there were also negative correlations between AdipoR to body weight and HOMA-IR (all, p<0.05). Conclusion: Our data suggest that puguntano could improve glucose metabolism and ameliorate insulin resistance and have anti-inflammatory effects mediated through AdipoR in T2DM.